2017
DOI: 10.1007/s12160-016-9843-3
|View full text |Cite
|
Sign up to set email alerts
|

Improving Collaborative Behaviour Planning in Adult Auditory Rehabilitation: Development of the I-PLAN Intervention Using the Behaviour Change Wheel

Abstract: Background The consequences of poorly managed hearing loss can be ameliorated with hearing aid use but rates of use are sub-optimal. The impact of audiologist behaviour on subsequent use, particularly over the long term, is unknown. Purpose This study aimed to describe the role of the behaviour change wheel in developing an intervention to introduce and embed particular clinical behaviours into adult hearing aid fitting consultations, within the framework of the Medical Research Council guidance on complex int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 58 publications
0
36
0
Order By: Relevance
“…The COM‐B model comprises six components that are hypothesized to drive behaviour, namely: physical capability (e.g., skills), psychological capability (e.g., knowledge), physical opportunity (e.g., time), social opportunity (e.g., social cues), reflective motivation (e.g., intentions), and automatic motivation (e.g., emotional reactions; Michie et al ., , ). The COM‐B model has been used previously in other areas of health care professional practice (Alexander, Brijnath, & Mazza, ; Barker, de Lusignan, & Cooke, ), but not across disciplines or in the domain of opportunistic behaviour change intervention. Using the COM‐B model to tailor the interview questions allowed us to: (1) obtain a broad understanding of the barriers and enablers to opportunistic behaviour change intervention, (2) use the Theoretical Domains Framework (TDF; described below) to identify the emergent themes that were generated from the data, and (3) link the respective components of the COM‐B model directly to the analytical framework (the TDF) to provide a focused analysis that highlighted the barriers and enablers to this area of professional practice (Cane, O'Connor, & Michie, ).…”
Section: Methodsmentioning
confidence: 99%
“…The COM‐B model comprises six components that are hypothesized to drive behaviour, namely: physical capability (e.g., skills), psychological capability (e.g., knowledge), physical opportunity (e.g., time), social opportunity (e.g., social cues), reflective motivation (e.g., intentions), and automatic motivation (e.g., emotional reactions; Michie et al ., , ). The COM‐B model has been used previously in other areas of health care professional practice (Alexander, Brijnath, & Mazza, ; Barker, de Lusignan, & Cooke, ), but not across disciplines or in the domain of opportunistic behaviour change intervention. Using the COM‐B model to tailor the interview questions allowed us to: (1) obtain a broad understanding of the barriers and enablers to opportunistic behaviour change intervention, (2) use the Theoretical Domains Framework (TDF; described below) to identify the emergent themes that were generated from the data, and (3) link the respective components of the COM‐B model directly to the analytical framework (the TDF) to provide a focused analysis that highlighted the barriers and enablers to this area of professional practice (Cane, O'Connor, & Michie, ).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, many of these theories use overlapping constructs and lack guidance for selecting the best one [36]. The Capability Opportunity Motivation-Behavior (COM-B) model was developed by integrating concepts from 19 frameworks of behavior change identified in a systematic review by Michie and colleagues (2011) [28] and has been applied successfully by others in the context of hearing health care [37, 38].…”
Section: Methodsmentioning
confidence: 99%
“…Use of these criteria allow researchers to look beyond the BCW and explore feasibility issues before trialling an intervention. Using the BCW to design interventions is becoming more common, and it has been successfully used to understand behaviour change in different contexts, such as sexual counselling [48], medication management [49,50], auditory rehabilitation [51], and physical activity [52]. Development of interventions using the full BCW to reduce workplace sitting however, is limited, with only the Stand More AT Work (SMArT) study found to target hospital office workers [53].…”
Section: Theoretical Framework Underpinning the Intervention Designmentioning
confidence: 99%